TNFα aggravates detrimental effects of SARS-CoV-2 infection in the liver - Lücke, Jöran; Nawrocki, Mikolaj; Schnell, Josa; Meins, Nicholas; Heinrich, Fabian; Zhang, Tao; Bertram, Franziska; Sabihi, Morsal; Böttcher, Marius; Blankenburg, Tom; Pfaff, Marie; Notz, Sara; et al. (Frontiers in Immunology, 2023)
Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This virus does not only lead to pulmonary infection but can also infect other organs such as the gut, the kidney, or the liver. Recent studies confirmed that severe cases of COVID-19 are often associated with liver damage and liver failure, as well as the systemic upregulation of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNFα). However, the impact these immune mediators in the liver have on patient survival during SARS-CoV-2 infection is currently unknown. Here, by performing a post-mortem analysis of 45 patients that died from a SARS-CoV-2 infection, we find that an increased expression of TNFA in the liver is associated with elevated mortality. Using publicly available single-cell sequencing datasets, we determined that Kupffer cells and monocytes are the main sources of this TNFα production. Further analysis revealed that TNFα signaling led to the upregulation of pro-inflammatory genes that are associated with an unfavorable outcome. Moreover, high levels of TNFA in the liver were associated with lower levels of interferon alpha and interferon beta. Thus, TNFα signaling in the infected SARS-CoV-2 liver correlates with reduced interferon levels and overall survival time.